FGD1 promotes tumor progression and regulates tumor immune response in osteosarcoma via inhibiting PTEN activity - Wu, Wei (Theranostics, 2020)
Rationale: Mesenchymal cell-derived osteosarcoma is a rare malignant bone tumor affecting children and adolescents. PTEN down-regulation or function-loss mutation is associated with the aggressive of osteosarcoma. Explicating the regulatory mechanism of PTEN might highlight new targets for improving the survival rate of osteosarcoma patients. Methods: The clinical relevance of FGD1 was examined by the TCGA data set, Western blotting and immunohistochemistry of osteosarcoma microarray slides. Functional assays, such as the MTS assay, colony formation assay and xenografts, were used to determine the biological role of FGD1 in osteosarcoma. The protein-protein interaction between FGD1 and PTEN was detected via co-immunoprecipitation. The relationship between FGD1 and PD-L1 was examined by Western blot analysis, RT-qPCR and immunohistochemistry. Results: In this study, analysis of the TCGA data set of sarcomas revealed that FGD1 was over-expressed with the highest P values. Then, we demonstrated that FGD1 was also abnormally up-regulated in osteosarcoma with unfavorable prognosis. Aberrant expressed FGD1 promoted the osteosarcoma tumor cell proliferation and invasion. Moreover, we found that FGD1 was participated in activating PI3K/AKT signaling pathway by interacting with PTEN. Finally, we showed that FGD1 was capable of regulating the tumor immune response via the PTEN/PD-L1 axis in osteosarcoma. Conclusions: Our data suggested that abnormally over-expressed FGD1 functions as an oncogenic protein to promote osteosarcoma progression through inhibiting PTEN activity and activating PI3K/AKT signaling. Notably, FGD1 increased PD-L1 expression in a PTEN dependent manner and modulated the sensitivity of immune checkpoint-based immunotherapy in osteosarcoma. Thus, FGD1 might be a potential target for improving the survival rate of osteosarcomas.